Emission characteristics of vehicles fueled by hydrogen-enriched syngas under no-load condition. (4th February 2020) - Meng, Fanbin; Wang, Hongde; Ma, Qingbang; Wang, Donghai; Lin, Jianfeng
Abstract: The emission characteristics of vehicles fueled by hydrogen-enriched syngas were investigated under the no-load condition. Syngas was produced using a fixed-bed gasification system. A Jetta car was modified and used for emission experiments with engine speed between 800 and 4800 rpm. Syngas compositions and emissions were analyzed using gas chromatography and a SPX-Tecnotest 488 exhaust gas analyzer, respectively. The results showed that syngas composition had significant effect on HC and NOx emission and air ratio (λ) was the key factor affecting CO emission. HC and NOx emissions increased significantly from 6 to 16 ppm and 139–832 ppm, respectively, when engine speed increased from 800 to 4800 rpm. CO emission did not significantly increase (lower than 0.5%) at engine speed less than 3200 rpm; at higher than 4800 rpm engine speed, CO emission increased rapidly (up to 2.7%). Highlights: Hydrogen-enriched syngas was obtained through biomass oxygen-enriched gasification. Emission characteristics of syngas-fueled vehicles were studied under no-load condition. Syngas composition had significant effect on HC and NOx emission. CO, HC, and NOx emissions increased significantly as engine speed increased. Exhaust gas emissions were much lower than the limit of China National Standard.